The Indian Sars-Cov-2 Variant: Role in the Reinfection and Immune System Response-Minireview - L. E. Weimer; G. Cattari; A. Binelli; E. Fanales Belasio; S. Piras; A. F. Proddighe; F. Sensi (Living with Sars-Cov-2 Variants. An Update in the Pandemic Era, 2021)
Diversification Of Sars-Cov-2 Due To Evolution And Adaptation Processes Has Been Observed Globally And Is Expected. Most Mutations That Emerge Will Not Provide A Selective Advantage To The Virus. However, Some Mutations Or Combinations Of Mutations May Do So, Such As Increased Transmissibility Through An Increase In Receptor Binding Or The Ability To Evade The Host Immune Response By Altering Surface Structures Recognised By Antibodies. Currently, Four Variants Designated As Variants Of Concern (Vocs) By Ecdc Are Under Surveillance In The Eu/Eea And Around The World (?.1.1.7, ?.1.1.7+E484k, B.1.351 And P.1). Another Nine Sars-Cov-2 Variants Are Considered Variants Of Interest (Voi) By Ecdc And Additional Variants Are Being Monitoring. First Reported In India In December 2020, Sars-Cov-2 Lineages B.1.617.1, B.1.617.2 And B.1.617.3 Have Been Increasingly Detected, These Lineages Are Distinct And Differ By Their Characteristic Mutations .The Aim Of This Threat Assessment Brief Is To Assess Potential Public Health Implications Of B.1.617 Variants For Eu/Eea Countries, With A Focus On Lineage B.1.617.2.